Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content: • The Level of Organizational Power Among Educational Zone Managers in the Capital Secretariat - Sana’a: from the Administrative Employees’ Perspective Mr. Youssef Qaid Sultan • Degree of Computer Teachers’ awareness of Artificial Intelligence Ethics in Riyadh Ms. Khulud Sulaiman Alfaraj ,Ms. Luluwah Saad Alshgrawe ,Ms. Amirah Mohammed Albalawi, Prof. Reem Abdulmohsen Alobaika • A Foresight Analysis of Structural Challenges in Implementing Oman’s National Education Strategy 2040 within a VUCA Environment and Human-Centered Artificial Intelligence Mr. Saif Hamad Aljaradi*, Ms. Zahra Rafat Joo ,Prof. Rahmatoallh Marzooghi, Prof. Jafar Torkzadeh, Dr. Elham Heydari • Teachers’ Attitudes Towards Teaching Mathematics to Third-Grade Male Students in Primary and Early Childhood Schools in Jeddah Ms. Atheer Abdullah Turki Alshehri, Co-Prof. Sama Fouad Khomais • Motivation for Achievement and Relationship to Distance Teaching during the Corona Pandemic by Kindergarten Teachers in Makkah-Al-Mukarrama Ms. Sumayyah Mubarak Alsharif , Dr. Hadeel Abdullah Akram • A proposed telepsychology program based on acceptance and commitment to develop post-traumatic growth among sons and daughters of duty martyrs at the secondary level in the Kingdom of Saudi Arabia Dr. Hanan Hamed Alsofyani, Dr. Noora Saad Alyemni • The Uses of Artificial Intelligence in Psychological Counseling and Guidance: An Analytical Study Ms. Hafsa Saleh Almudhi, Ms. Bara Mohammed Albogami , Ms. Nojod Melfi Alharbi, Ms. Maryam Moteeb Almuteri, Dr. Nouf Walid Azab • A proposed model to reduce the impacts of educide on school education in Gaza Strip during the 2023 war Mr. Bahaa D. Alghirbawi